2021
DOI: 10.1055/s-0041-1730426
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Metastasis from Colorectal Adenocarcinoma

Abstract: Introduction Ovarian metastases of gastrointestinal origin, also called Krukenberg tumors, have a guarded prognosis. Physicians need to look for alternatives in diagnosis and treatment for this clinical condition in order to improve the outcome of the patients. Objectives To report the experience of the authors in the treatment of these patients, and to perform a review of the literature on the epidemiology, clinical presentation, diagnosis, treatment, and prognosis for ovarian metastases from colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Other reports have shown that OM results in shortened survival compared with patients with only extra-ovarian metastases, and that resection of OM could result in improved overall survival. 8,44,[49][50][51] The reduced chemotherapeutic sensitivity, as well as factors mentioned above, could therefore be seen as arguments in favor of prophylactic salpingo-oophorectomy, or a metastasectomy, when OM occurs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other reports have shown that OM results in shortened survival compared with patients with only extra-ovarian metastases, and that resection of OM could result in improved overall survival. 8,44,[49][50][51] The reduced chemotherapeutic sensitivity, as well as factors mentioned above, could therefore be seen as arguments in favor of prophylactic salpingo-oophorectomy, or a metastasectomy, when OM occurs.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] Alternatively, when oophorectomy is not eligible, PSO could be waived and after adequate counseling prophylactic salpingectomy could be done safely during elective surgery to prevent ovarian cancer. [51][52][53] Several other disciplines already perform surgery to prevent OM. Gynecologists generally perform oophorectomies in patients operated for endometrial cancer to reduce the risk of OM which is approximately 6% in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations